Controversial Regulation of Gene Expression and Protein Transduction of Aquaporins under Drought and Salinity Stress - Lucía Yepes-Molina; Gloria Bárzana; Micaela Carvajal (Plants, 2020)
Enhancement of the passage of water through membranes is one of the main mechanisms via which cells can maintain their homeostasis under stress conditions, and aquaporins are the main participants in this process. However, in the last few years, a number of studies have reported discrepancies between aquaporin messenger RNA (mRNA) expression and the number of aquaporin proteins synthesised in response to abiotic stress. These observations suggest the existence of post-transcriptional mechanisms which regulate plasma membrane intrinsic protein (PIP) trafficking to the plasma membrane. This indicates that the mRNA synthesis of some aquaporins could be modulated by the accumulation of the corresponding encoded protein, in relation to the turnover of the membranes. This aspect is discussed in terms of the results obtained: on the one hand, with isolated vesicles, in which the level of proteins present provides the membranes with important characteristics such as resistance and stability and, on the other, with isolated proteins reconstituted in artificial liposomes as an in vitro method to address the in vivo physiology of the entire plant.